REPRESENTASI PERAN PEREMPUAN PADA QS. AL-AHQAF (46): 15 DAN QS. AL-NISA’ (4): 34: DEKONSTRUKSI MAKNA SEMIOTIKA ROLAND BARTHES - Zuhriyandi (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2024)
This research examines the representation of women’s roles in the Koran through Roland Barthes’ semiotic deconstruction approach, with a focus on the QS. al-Ahqaf (46):15 and QS. al-Nisa (4):34. This research is a qualitative approach using Roland Barthes’ semiotic analysis, to reveal hidden layers of meaning in these sacred texts. QS. al-Ahqaf (46): 15 describes the role of women as mother figures who symbolize sacrifice, steadfastness, and compassion, as well as educating children with spiritual and moral values. Meanwhile, in QS. al-Nisa’ (4): 34 emphasizes the importance of respecting and appreciating the role of women in the context of the family and society. The results of this research show that the role of women in the Koran includes biological, spiritual, and emotional aspects. Barthes’ semiotic approach also helps reveal meanings that may be overlooked in traditional interpretations, as well as highlighting the importance of education, empowerment, collaboration, and protecting women’s human rights. This research provides new insights into the understanding of sacred texts in diverse contemporary contexts, as well as their interpretive implications for gender roles in Islamic societies.